PEMETAAN BENGKEL SEPEDA MOTOR DI KECAMATAN KOTO TANGAH KOTA PADANG - harpendi pendi bahri; yurni suasti; Triyatno Triyatno (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine the distribution of motorcycle repair shops in Koto Tangah District, Padang City. This type of research is quantitative descriptive. Data collected through field surveys and interviews. Data analysis techniques using the application (software) ArcGIS Geographic Information System 10.3. The distribution patterns of motorcycle workshops in the Koto district are analyzed by analysis of the nearest neighbor (nearest neighbor analys). The results showed that the distribution pattern of motorcycle workshops in Koto Tangah Subdistrict was clustered with a total of 107 motorcycle workshop businesses. 101 motorcycle repair shop business status is free workshop, 6 motorcycle workshop business with dealer and representative workshop found in Koto Tangah District, Padang City. Turnover of sales sparepart and service of workshop businesses in the Koto Tangah Subdistrict of Padang City is Rp 500,000 - Rp.36,000,000 with turnover of sales sparepart of motorcycle Rp 500,000 - 5.500,000 with 84 workshops totaling 78%, turnover of sales service of motorcycle 1,000,000 - 6,000,000 with 4 7 workshops or 44%, out of 107 workshop businesses in the Koto Tangah District of Padang City.